2023
DOI: 10.1111/ene.16059
|View full text |Cite
|
Sign up to set email alerts
|

Rates of John Cunningham virus seroconversion greatly reduced in natalizumab‐treated patients during COVID‐19‐related lockdowns

Chris Dwyer,
Sifat Sharmin,
Tomas Kalincik

Abstract: Background and purposeThis study was undertaken to retrospectively compare rates of John Cunningham virus (JCV) seroconversion in natalizumab‐treated patients before and during COVID‐19‐related community restrictions. Natalizumab is highly effective therapy for relapsing–remitting multiple sclerosis. Prolonged exposure to natalizumab in JCV‐positive patients can cause progressive multifocal leukoencephalopathy, a potentially fatal brain infection. Serial assessment of JCV status is required for patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Elevated levels of neprilysin in prostate cancer patients infected with JCV could potentially function as a biomarker indicating disease aggressiveness or prognosis [40,41]. Monitoring neprilysin levels in conjunction with other clinical parameters may assist in risk assessment and tailored treatment strategies [42,43] and regularly monitoring neprilysin levels, particularly in individuals with JCV infection, can offer crucial prognostic insights and help tailor treatment plans to suit each patient's needs [44,45] and these discoveries could impact the assessment of risk, prediction of outcomes, and decisions regarding treatment for individuals with prostate cancer [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of neprilysin in prostate cancer patients infected with JCV could potentially function as a biomarker indicating disease aggressiveness or prognosis [40,41]. Monitoring neprilysin levels in conjunction with other clinical parameters may assist in risk assessment and tailored treatment strategies [42,43] and regularly monitoring neprilysin levels, particularly in individuals with JCV infection, can offer crucial prognostic insights and help tailor treatment plans to suit each patient's needs [44,45] and these discoveries could impact the assessment of risk, prediction of outcomes, and decisions regarding treatment for individuals with prostate cancer [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…JCPyV seropositivity rates did not follow this trend and remained consistent instead, regardless of isolation measures [ 73 ]. On the other hand, another study, which examined JCPyV seropositivity rates in multiple sclerosis (MS) patients during COVID-19, discovered that conversion rates declined during lock down [ 74 ]. Other studies have found an increasing prevalence of JCPyV LTAg in colorectal cancers [ 75 , 76 , 77 , 78 , 79 ].…”
Section: How Is Jcpyv Transmitted?mentioning
confidence: 99%